Endovascular treatment of acute type A aortic dissection in a nonagenarian: stabilization of a short covered stent using a bare-metal stent. (22nd August 2019) - Wamala, Isaac; Heck, Roland; Falk, Volkmar; Buz, Semih
Abstract: Endovascular treatment is a viable alternative therapy in high-risk patients with acute type A aortic dissection. However, the optimal endovascular treatment strategy is still evolving. Herein, we present a case of a 91-year-old man who successfully underwent repair of an ascending aortic dissection using a stent-in-stent technique. At 1-year follow-up, the stent demonstrated repair durability.